2018
DOI: 10.1016/j.molcel.2018.06.016
|View full text |Cite|
|
Sign up to set email alerts
|

Quantifying Nucleation In Vivo Reveals the Physical Basis of Prion-like Phase Behavior

Abstract: Protein self-assemblies modulate protein activities over biological timescales that can exceed the lifetimes of the proteins or even the cells that harbor them. We hypothesized that these timescales relate to kinetic barriers inherent to the nucleation of ordered phases. To investigate nucleation barriers in living cells, we developed distributed amphifluoric FRET (DAmFRET). DAmFRET exploits a photoconvertible fluorophore, heterogeneous expression, and large cell numbers to quantify via flow cytometry the exte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
177
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(200 citation statements)
references
References 96 publications
(114 reference statements)
2
177
0
Order By: Relevance
“…Some data support the hypothesis that the [PIN + ] aggregates of RNQ1 cross-seed aggregation of heterologous proteins such as SUP35 and polyQ. Likewise some, but not all evidence suggests that the [PIN + ] aggregates bind proteins such as chaperones that would otherwise inhibit aggregation of the heterologous SUP35 or polyQ protein, thereby enhancing their aggregation [18][19][20][21][22][23][24][25]27] We recently showed that toxicity of TDP-43 and FUS is enhanced by the presence of [PIN + ] [37,57]. Both of these proteins contain Q/N-rich regions and co-aggregate with polyQ disease protein alleles of huntingtin [64,65].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Some data support the hypothesis that the [PIN + ] aggregates of RNQ1 cross-seed aggregation of heterologous proteins such as SUP35 and polyQ. Likewise some, but not all evidence suggests that the [PIN + ] aggregates bind proteins such as chaperones that would otherwise inhibit aggregation of the heterologous SUP35 or polyQ protein, thereby enhancing their aggregation [18][19][20][21][22][23][24][25]27] We recently showed that toxicity of TDP-43 and FUS is enhanced by the presence of [PIN + ] [37,57]. Both of these proteins contain Q/N-rich regions and co-aggregate with polyQ disease protein alleles of huntingtin [64,65].…”
Section: Discussionmentioning
confidence: 84%
“…For example, the endogenous yeast prion [PIN + ], which is an amyloid form of the RNQ1 protein, promotes the de novo aggregation of the SUP35 protein to form the [PSI + ] prion. This could occur by cross-seeding or by sequestration of proteins such as chaperones by the amyloid [PIN + ] prion [8,[16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, advanced fluorescence correlation spectroscopy measurements were used to understand the diffusion of molecules and corresponding organization of MLOs . In other work, an advanced application of FRET methodology enabled measurements of nucleation for prion‐like proteins in live cells . The FRET method used controlled photoconversion of a fluorescent protein from donor to acceptor species directly in cells, thus generating the FRET dye pair in situ and avoiding variations with protein concentration and individual cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Wtf4 proteins localize as puncta of varying sizes, so we hypothesized that the proteins 259 assemble into aggregates. To explore the nature of the Wtf4 protein assemblies, we utilized the 260 recently developed Distributed Amphifluoric FRET (DAmFRET) assay (Khan et al, 2018). This 261 approach looks for FRET between red and green fluorophores in a partially photoconverted Figure 1A).…”
mentioning
confidence: 99%
“…Recovery After Photobleaching (half-FRAP) (Khan et al, 2018;Zhang et al, 2015). This 372 analysis revealed that the Wtf4 antidote -mCherry aggregate has very low internal mobility and is 373 thus more solid-like than liquid-like ( Figure 5B).…”
mentioning
confidence: 99%